The Use of Comics to Allow Creativity and Promote Higher Order Thinking Skills - . Badriah (Journal of English Language Learning, 2017)
AbstractThe study aimed to find out the effect of the use of comics on 11th elective program graders of SMAN 2 Cianjur in their Narrative text understanding performance as well as their attitudes towards it. The results show that visual images in form of student-generated comic strips allow for creativity where students can express ideas by images combined with text, and promote higher order thinking skills (analyzing, evaluating, creating) through student-centered work. From its findings, the study concluded that comics is: 1) effective for constructive activities such as writing and speaking and 2) benefitted slow learners as they can take advantage of visual guide to practice target-language use.Keywords: Comics, Narrative, higher order thinking skills